Mesenchymal Stromal Cell Therapy for Respiratory Complications of Extreme Prematurity - Thébaud, Bernard (American Journal of Perinatology, 2018)
Bronchopulmonary dysplasia remains the main complication of extreme preterm birth. Research over the past 10 years suggests the potential for stem cell-based therapies to prevent and/or restore organ damage in extreme preterm infants. Mesenchymal stromal cells, in particular, have advanced as the forerunner among various cell therapies based on very promising preclinical studies in animal models of neonatal lung injury. Early phase clinical trials are now underway to determine the safety and feasibility of this cell therapy in preterm infants at risk of developing bronchopulmonary dysplasia. This review will summarize the current rationale for testing mesenchymal stromal cells in this patient population and highlight the gaps in our knowledge to safely harness the full repair potential of cell-based therapies.
Keywords: lung; injury; stem cells; regenerative medicine; preterm birth